Contexts and gender: Looking back and thinking forward - Friederike Welter (Institut für Mittelstandsforschung (IfM) Bonn, 2020)
Purpose: The paper aims to illustrate the main contributions of the context-gender discussion in entrepreneurship research and its main developments over time, in order to identify promising future research avenues. Design/Methodology/Approach: The paper builds on the author's extensive knowledge of the context-gender debate and on several recent overviews and reviews of the debate. It is written as essay, introducing its main themes through a personal reflection and complemented by a selective review of research on gendered contexts and women's entrepreneurship. Findings: The context-gender discussion has moved forward. In a first wave of context-gender studies, research contextualized gender, considering the impact of contexts on women's entrepreneurship. Nowadays, research studies how contexts are gendered and how they are constructed in gendered ways, through for example, words, images, cognitions, as well as how women entrepreneurs can impact on and enact their contexts. Originality/Value: This paper contributes novel insights into contextualizing gender and gendering contexts. It is unique in suggesting that a perspective on gendering contexts will allow to explore the diversity of entrepreneurship and further develop theories related to contexts and gender. – – Das Working Paper zeigt auf, wie sich die Gender-Kontext-Debatte von ihrem anfänglichen Fokus auf die Kontextualisierung der Geschlechter weiter zur Berücksichtigung des Geschlechts bei der Kontextbetrachtung entwickelt hat.
Keywords: 330; context; contextualizing gender; gendering contexts; contextual entrepreneurship